iTRAQ Proteomic Analysis of Wheat (Triticum aestivum L.) Genotypes Differing in Waterlogging Tolerance - Yang, Rui; Li, Murong; Harrison, Matthew Tom; Fahad, Shah; Wei, Mingmei; Li, Xiu; Yin, Lijun; Sha, Aihua; Zhou, Meixue; Liu, Ke; Wang, Xiaoyan (Frontiers in Plant Science, 2022)
Waterlogging is one of the major abiotic stresses limiting wheat product. Plants can adapt to waterlogging with changes in morphology, anatomy, and metabolism. Many genes and proteins play critical roles in adaptation to waterlogging. In this study, the iTRAQ-based proteomic strategy was applied to identify the waterlogging-responsive proteins in wheat. A total of 7,710 proteins were identified in two wheat varieties, XM 55 (waterlogging-tolerant) and YM 158 (waterlogging-sensitive), at anthesis under waterlogging or not. Sixteen proteins were differentially accumulated between XM 55 and YM 158 under waterlogging with cultivar specificity. Of these, 11 proteins were up-regulated and 5 proteins were down-regulated. The up-regulated proteins included Fe-S cluster assembly factor, heat shock cognate 70, GTP-binding protein SAR1A-like, and CBS domain-containing protein. The down-regulated proteins contained photosystem II reaction center protein H, carotenoid 9,10 (9',10')-cleavage dioxygenase-like, psbP-like protein 1, and mitochondrial ATPase inhibitor. In addition, 9 proteins were responsive to waterlogging with non-cultivar specificity. These proteins included 3-isopropylmalate dehydratase large subunit, solanesyl-diphosphate synthase 2, DEAD-box ATP-dependent RNA helicase 3, and 3 predicted or uncharacterized proteins. Sixteen out of the 28 selected proteins showed consistent expression patterns between mRNA and protein levels. This study revealed that the proteins were differential accumulated between the two contrast waterlogging wheat varieties in response to waterlogging, which provide valuable insights into wheat response to waterlogging stress. The identified differentially accumulated protein might be applied to develop waterlogging tolerant wheat.